Investigating the causes and consequences of controlled rest on the flight deck - Hilditch, Cassie J.; Arsintescu, Lucia; Pradhan, Sean; Gregory, Kevin B.; Flynn-Evans, Erin E. (Frontiers in Environmental Health, 2024)
Introduction Fatigue is a known issue in aviation due to long and irregular working hours. In some regions, pilots are permitted to sleep during a controlled rest period on the flight deck to manage unexpected sleepiness. We aimed to determine: (1) the relative influence of pre-flight sleep-wake history and time of day on the likelihood to take controlled rest; (2) whether neurobehavioral measures taken pre-flight are predictive of controlled rest use in-flight; and (3) the impact of controlled rest on neurobehavioral measures at top-of-descent. Methods Data from 120 long (>6 h flight duration), unaugmented (two-pilot) flights were analyzed (n = 31 pilots). Pilots wore actiwatches and completed sleep logs before and during trips. At pre-flight and top-of-descent, pilots completed a 5-min psychomotor vigilance task (PVT) and Karolinska Sleepiness Scale (KSS). A series of mixed-effects models with relevant covariates were conducted to assess the likelihood of controlled rest based on several predictors and the impact of controlled rest on outcome measures at top-of-descent. Results Pilots were more likely to take controlled rest on night flights [p = .01, η2p = .13, OR = 13.81, 95% CI: (1.99, 95.80)] and when pre-flight sleepiness ratings were higher [p = .01, η2p = .14, OR = 4.14, 95% CI: (1.48, 11.57)]. Pilots who took controlled rest had faster response speeds [1000/reaction time (ms)] [p = .03, η2p = 0.07; estimated marginal mean (EMM) = 4.19, standard error (SE) = 0.07, 95% CI: (4.08, 4.29)] than those who did not [EMM = 4.00, SE = 0.05, 95% CI: (3.86, 4.14)]. Discussion Our results suggest that taking controlled rest may improve vigilant attention at critical phases of flight and may be a useful fatigue management tool, particularly during unaugmented night flights. Further research is needed to determine the impact of psychological and cultural influences on controlled rest and to understand how the policy is applied in practice.